(untitled) (Experimental biology, 2025)
As a result of floristic studies conducted in Shymkent city, it was found that the species diversity of lichens and mosses is significantly limited compared to humid regions. This situation is closely related to the deservedly dry climate of the region and increasing urbanization. Special botanical studies are needed to accurately identify lichen and moss species and to study their distribution patterns. These studies provide opportunities to map the distribution of lichens and mosses and to assess their ecological significance. Urbanization of cities and climate change have a negative impact on the populations of these plants. The distribution of lichens is sparse, with species belonging to the genera Candelaria, Xanthoria, Physcia, Parmelia, Polycauliona being more common.